(untitled) (Philosophy and Progress, 2024)
Mysticism is a spiritual search for hidden truth or wisdom that aims to unite with the metaphysical realm. Mysticism is a direct experience of oneness with God. It is a diverse set of practices, discourses, teachings, articles, texts, institutions, traditions, and experiences related to the instruction of human transformation. Mysticism encompasses everything associated with God. Mystical experiences are unique to each individual. This paper delves into the mystical thoughts of two multi-genius thinkers, the greatest philosophers and mystical poets: Rabindranath Tagore and Muhammad Iqbal. It also shows the relationship between man and God in the writing of Tagore and Iqbal. Also, it deals with how Tagore and Iqbal combine nature, different aspects of the self, and images of the divine. They hold that God’s presence permeates all of creation and that mysticism and humanism are the primary sources of an individual’s spiritual power. They think that God is within man, and man is a reflection of this divine spirit, which is God. Tagore imparts a system of Indian mystical thought in which the Gita’s theism, Vedic metaphysics, the Upanishad’s teachings, the mystical philosophy of the Bauls, the doctrine of love of Vaishnava, and Sufism exist in synthesis. Iqbal emphasizes that the ultimate goal of human life is to accomplish the will of the Almighty. Tagore and Iqbal’s writing contains many similar ideas, images, techniques, and analyses. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 183-214